Pengaruh Pelatihan Kerja Dan Keselamatan Dan Kesehatan Kerja (K3) Terhadap Produktivitas Kerja Karyawan PT Inkabiz Indonesia Tangerang Selatan - Feriah Triana Reisa Mega; Rian Sri Rahayu (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of job training and occupational health and safety (OHS) on the work productivity of employees at PT Inkabiz Indonesia in South Tangerang. The research method used is the quantitative analysis method with an associative approach. The sample used in this study consisted of 82 employees of PT Inkabiz Indonesia. The data analysis used in this study includes: data quantity test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test, and hypothesis test. (uji t dan uji F). Partially, job training has a significant effect on work productivity, as evidenced by the regression equation Y = 20.908 + 0.470X1, with a correlation coefficient of 0.478, indicating a moderate relationship between the two variables. The t-value of 4.871 > t-table 1.990 with a significance value of 0.000 < 0.05 means H0 is rejected and H1 is accepted. Partially, occupational safety and health significantly affect work productivity, as evidenced by the regression equation Y = 22.591 + 0.452X2, with a correlation coefficient of 0.470, indicating a moderate relationship between the two variables. The t-value of 4.769 > t-table 1.991 with a significance value of 0.000 < 0.05 means H0 is rejected and H2 is accepted. Simultaneously, job training and occupational safety and health significantly affect work productivity, as evidenced by the regression equation Y = 16.326 + 0.313X1 + 0.289X2, with a correlation coefficient of 0.542, indicating a moderate relationship. The F-value of 16.431 > F-table 2.720 with a significance value of 0.000 < 0.05 means H0 is rejected and H3 is accepted